2005
DOI: 10.1177/0885412204271878
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inner Ring Suburbs in Metropolitan Smart Growth Strategies

Abstract: Strengthening the effectiveness of metropolitan smart growth policies requires an understanding of the role and conditions of inner ring suburbs. Nevertheless, the issue of the deterioration of the inner ring suburbs has only recently received significant consideration by urban scholars and policy makers. In this article, the authors review the literature on metropolitan formation and the smart growth movement to critically assess how well it characterizes and explains the evolution of inner ring suburbs, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…To differentiate suburban communities, some researchers have referred to the concept of ‘suburban tiers’, which they have categorized according to development periods and neighborhood characteristics (Jackson, 1985; Bollens, 1988; Orfield, 1997; Freilich, 1999; Lucy and Phillips, 2000; Lee and Leigh, 2005). Using the concept of suburban tiers, urban scholars and policymakers have differentiated suburbs into separate communities.…”
Section: Transformation Of the Us Metropolitan Structure And Intra‐mementioning
confidence: 99%
“…To differentiate suburban communities, some researchers have referred to the concept of ‘suburban tiers’, which they have categorized according to development periods and neighborhood characteristics (Jackson, 1985; Bollens, 1988; Orfield, 1997; Freilich, 1999; Lucy and Phillips, 2000; Lee and Leigh, 2005). Using the concept of suburban tiers, urban scholars and policymakers have differentiated suburbs into separate communities.…”
Section: Transformation Of the Us Metropolitan Structure And Intra‐mementioning
confidence: 99%
“…wildfires and hurricanes are almost always followed by rebuilding). Recent analyses have shown that the only places where sustained, substantial loss of housing in the US occurs are in areas of widespread property abandonment at the center of large urban areas that are decentralizing (Lee and Leigh 2005); these areas affect a very small proportion of the landscape compared to areas where houses remain or are becoming more numerous. Urban core property abandonment is even more unlikely in Oregon because the state encourages new development within city centers (Wassmer and Baass 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Density gradients, also called density-decay models, reveal a picture of density distribution around centres. Density-decay profiles also have been used to explore historical changes and trends (e.g., Filion, Bunting, McSpurren, & Tse, 2004;Griffith & Wong, 2007;Lee & Leigh, 2005;Waddell, 1994). Modifications of this method encompass diverse definitions of centres, density types and decay functions (linear versus non-linear), which…”
Section: Literature Reviewmentioning
confidence: 99%